The Effect of Forest Area, Energy Consumption, Control of Corruption, and Economic Growth on Carbon Emissions in G7 Countries - Heryadi, Wasji; Yasmin Maulida, Sabila; Meiliana Dewi, Shakira (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2024)
This research aims to determine the influence of Forest Area, Energy Consumption, Control of Corruption, and Economic Growth on Carbon Emissions. This study uses panel data published by the World Bank and Our World in Data for the 2014-2020 period in the G7 countries, namely America, Italy, United Kingdom, France, Japan, Canada and Germany. In this study, the carbon emissions variable is used as the dependent variable. Forest area, energy consumption, Control of Corruption, and economic growth as independent variables. The analysis technique for this panel research uses panel data regression with a fixed effect model (FEM) approach. The research results show that forest area, energy consumption simultaneously and partially influence carbon emissions in G7 countries. Meanwhile, control of corruption and economic growth have a positive and insignificant effect on carbon emissions.